Level of knowledge and infection control practice among bsn III old curriculum students in the nicu of a tertiary hospital in muntinlupa: basis for clinical enchancement program/ Ruffa Capio, Cherrie-Ann Espiritu, Maria Kathrina Hubahib, Pedro Perigrino Lacaden, and Joanne Ashley Layug. - Capio, Ruffa; Espiritu, Cherrie-Ann; Hubahib, Maria Kathrina; Lacaden, Pedro Perigrino; Layug, Joanne Ashley (Paranque City; Olivarez College, 2011)
This study used the descriptive method of research. The researchers selected their respondents through purposive sampling. In purposive sampling, a sample is deliberately chosen by using a sampling plan that screens out materials with certain characteristics and/or selects only material with other relevant characteristics (Devore & Peck 2005). It was utilized by selecting fifty third year BSN students enrolled under the old curriculum nursing program who had been exposed in the NICU area. The tool used by the researchers included a self- made questionnaire and checklist performance utilized to gather data that was analyzed in this research. The researchers used the following statistical treatment: Weighted Mean, Pearson's Product Moment of Correlation and a Likert Scale. Specifically, this study sought to answer the following questions: 1. What is the level of knowledge on infection control among respondents in terms of: 1.1 Hand Hygiene 1.2 Isolation Precaution 1.3 Sterilization Technique 1.4 Personal Protective Equipment 2. To what extent does the respondents practice infection control in terms of. 2.1 Hand Hygiene 2.2 Isolation Precaution 2.3 Sterilization Technique 2.4 Personal Protective Equipment 3. Is there a significant relationship between the level of knowledge and practice on infection control among the respondents? 4. Based from the results of the findings, what would be the proposed clinical enhancement program? The following are findings of the study: 1. Level of Knowledge The level of knowledge of the student respondents on hand hygiene is moderately knowledgeable with a (mean = 1.88), whereas in isolation precaution (mean = 1.20), sterilization technique (mean = 1.36), and personal protective equipment (mean = 1.16). The data showed that the respondents are not knowledgeable in the areas assessed with a weighted mean of 1.40. 2. Level of Practice 2.1. With regard to hand washing, all the necessary procedures are always performed in the NICU area of the said institution with a mean of 3.73. 2.2. Environmental Cleaning/ Sanitation protocols are always executed except making the rooms well ventilated and dust-free which are sometimes done by the student nurses. This obtained a weighted mean of 3.62 23. All the respondents are aware of the importance of a clean environment which makes them always observe the proper waste disposal protocol. The respondents obtained a mean of 3.62. 24 The standard precaution procedures are always performed by the respondents, obtaining a mean of 3.68 3. Relationship between the level of knowledge and infection control practice among respondents. Findings show that there is a significant relationship between the level of knowledge and infection control practice among the respondents as the level of correlation is above 0.05. The level of correlation obtained was 0.69. Thus, the null hypothesis is rejected. 4. Based from the result of the findings, what could be the proposed Clinical Enhancement Program? The data gathered showed that the respondents were not knowledgeable in terms of the infection control strategies utilized in the study. The researchers, therefore, would recommend that the clinical enhancement program would focus more on expanding the cognitive knowledge of the students concerning infection control. Since they lack the necessary information needed, transfer of knowledge must be more effective by creating a program that would specifically answer those which the students lack. From the findings of the study, the following conclusions were drawn 1. Knowledge deficit existed in all areas Infection Control Strategies among samples utilized in the study 2. Student respondents were able to exhibit a high frequency on infection control in the NICU area: 3. The data gathered gained a significant relationship between the level of knowledge and infection control practice among the respondents The findings indicate that student's lack knowledge on infection control in terms of: a) Hand Hygiene, b.) Isolation Precaution, c) Sterilization Technique, and d.) Personal Protective Equipment. Based on the findings and conclusions of the study, the researchers present the following recommendations: 1. Those nursing students who are and who will undergo hospital duties or internship must equip themselves with the necessary preventive measures to prevent from acquiring the most common diseases such as coughs, colds, and others. Since the most common disease acquired in the hospital setting is about respiratory problem, which is a contagious disease, we recommend that the student nurses must at all times, if possible, keep a 3 feet distance among patients and should always wear masks while interacting with the patients. 2 Students must always perform hand washing before, during, after or as long as necessary to prevent from acquiring and transmitting diseases, since handwashing has been a highly effective prevention for nursing students based on the study. It is also the oldest, simplest, and cheapest way to control the spread of infectious organisms. 3. Since the preventive strategies are highly effective, the researchers recommend that they should also see to it that they follow standard precautions and proper ways of using the preventive measures since it may affect the effectiveness of utilizing infection control strategies. The researchers would also recommend the formulation of a clinical enhancement program focusing on increasing the cognitive knowledge of the student nurses who are going to be exposed in the NICU area. In order to do this, the researchers would present the data to the clinical coordinator who will then create the appropriate program for the students. 5. The researchers would recommend the development of learning program which is necessary in achieving the deficiency in the cognitive and psychomotor domain of learning of the respondents. The responsibility of the instructor is to promote the learners relevant knowledge to underpin the development of skills Attempts should be made to ensure that the learner is taught in such a way that it allows them to construct learning in a simulated context and then apply it into real situation. The focus should be on the leamer's understanding the process of acquisition rather than mere practice. They should develop guidelines such as audio-visual materials (i.e. video tapes, slides, etc) on infection control strategies
Undergraduate Thesis